Cryogel Scaffold-Mediated Delivery of Adipose-Derived Stem Cells Promotes Healing in Murine Model of Atrophic Non-Union - Hixon, Katherine R.; Katz, Dakota B.; McKenzie, Jennifer A.; Miller, Anna N.; Guilak, Farshid; Silva, Matthew J. (Frontiers in Bioengineering and Biotechnology, 2022)
Non-union is defined as the permanent failure of a bone to heal and occurs clinically in 5% of fractures. Atrophic non-unions, characterized by absent/minimal callus formation, are poorly understood and difficult to treat. We recently demonstrated a novel murine model of atrophic non-union in the 3.6Col1A1-tk (Col1-tk) mouse, wherein dosing with the nucleoside analog ganciclovir (GCV) was used to deplete proliferating osteoprogenitor cells, leading to a radiographic and biomechanical non-union after the mid-shaft femur fracture. Using this Col1-tk atrophic non-union model, we hypothesized that the scaffold-mediated lentiviral delivery of doxycycline-inducible BMP-2 transgenes would induce osteogenesis at the fracture site. Cryogel scaffolds were used as a vehicle for GFP+ and BMP-2+ cell delivery to the site of non-union. Cryogel scaffolds were biofabricated through the cross-linking of a chitosan–gelatin polymer solution at subzero temperatures, which results in a macroporous, spongy structure that may be advantageous for a bone regeneration application. Murine adipose-derived stem cells were seeded onto the cryogel scaffolds, where they underwent lentiviral transduction. Following the establishment of atrophic non-unions in the femurs of Col1-tk mice (4 weeks post-fracture), transduced, seeded scaffolds were surgically placed around the site of non-union, and the animals were given doxycycline water to induce BMP-2 production. Controls included GFP+ cells on the cryogel scaffolds, acellular scaffolds, and sham (no scaffold). Weekly radiographs were taken, and endpoint analysis included micro-CT and histological staining. After 2 weeks of implantation, the BMP-2+ scaffolds were infiltrated with cartilage and woven bone at the non-union site, while GFP+ scaffolds had woven bone formation. Later, timepoints of 8 weeks had woven bone and vessel formation within the BMP-2+ and GFP + scaffolds with cortical bridging of the original fracture site in both groups. Overall, the cell-seeded cryogels promoted osseous healing. However, while the addition of BMP-2 promoted the endochondral ossification, it may provide a slower route to healing. This proof-of-concept study demonstrates the potential for cellularized cryogel scaffolds to enhance the healing of non-unions.